Reflexões sobre o turismo cultural na 'Cidade Maravilhosa' - Cunha, Erika Conceição Gelenske (2008)
The World Tourism Organization - WTO (2003) asserts that a new stage on tourism is arising. On a post-modern world, the touristic movement more and more searched for the 'different', the 'other', thus, stimulating a motivation for the 'tourism based on the cultural legacy' (BARRETTO, 2000). Along with this, the Ministry of Tourism has created in 2006, a typology of tourism, based on the motivations for the travelling accomplishment, or in the market segmentation. This project, which intends to 'organize the tourism for planning, management and market ends' separates the tourism in five priority segments, among them is the cultural segment. Thus, the current essay tries to accomplish some reflections on the cultural tourism in the city of Rio de Janeiro, city which has a main role in the Brazilian history of political and cultural life. In this regard, first a survey of the several concepts which imbricate themselves with the cultural tourism has been made: culture, cultural heritage, memory, authenticity, identities and consumption. On a second stage, by means of a field research, the touristic supply was delineated, and it was analyzed how the cultural tourism is currently explored by the main local telephonic operator companies. Also, a focus on a group of graduates in this field was created, in order to debate the theme in a critical and dialectical manner. This material analysis allowed a gathering of the cultural tourism habits in the 'Cidade Maravilhosa' ('Wonderful City'), creating reflections on the efficient development of the touristic activity in the city of Rio de Janeiro.